2017
DOI: 10.1371/journal.pone.0184800
|View full text |Cite
|
Sign up to set email alerts
|

Success rates in smoking cessation: Psychological preparation plays a critical role and interacts with other factors such as psychoactive substances

Abstract: IntroductionThe aim of this study was to identify factors associated with the results of smoking cessation attempts.MethodsData were collected in Clermont-Ferrand from a smoking cessation clinic between 1999 and 2009 (1,361 patients). Smoking cessation was considered a success when patients were abstinent 6 months after the beginning of cessation. Multivariate logistic regression was used to investigate the association between abstinence and different factors.ResultsThe significant factors were a history of de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
13
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 50 publications
(38 reference statements)
6
13
0
2
Order By: Relevance
“…This was in line with the finding of a meta-analysis of 42 trials by Hitsman et al, in which major depression had a moderate adverse effect on quitting smoking [53]. This finding was also in agreement with previous studies that concluded that patients who quit smoking were less likely to have depression and that depression greatly decreased the likelihood of quitting smoking [29,30].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This was in line with the finding of a meta-analysis of 42 trials by Hitsman et al, in which major depression had a moderate adverse effect on quitting smoking [53]. This finding was also in agreement with previous studies that concluded that patients who quit smoking were less likely to have depression and that depression greatly decreased the likelihood of quitting smoking [29,30].…”
Section: Discussionsupporting
confidence: 92%
“…Smoking-related variables include tobacco dependence, the baseline number of cigarettes smoked per day, the number of previous quit attempts, motivation to quit, and the proportion of smokers in the household, all of which might influence the success of quitting smoking [18,22,[27][28][29]. Predictors of successful quitting include lower levels of depression [29,30]. Better designed observational studies are needed to determine the factors that are associated with successfully quitting smoking in CR attendees.…”
Section: Introductionmentioning
confidence: 99%
“…The challenge here is to motivate those at risk to actively participate in preventive measures and to overcome the high dropout rate of lifestyle interventions. A personalized motivational approach, taking into account the individual psychosocial background, would likely improve the intervention success 43. In addition, specific preventive measures against comorbid diseases (for example treatment of hypertension or dyslipidaemia) have to be taken into account, and alpha1 antitrypsin augmentation therapy may be considered in deficient individuals.…”
Section: Development Of Copdmentioning
confidence: 99%
“…El consumo de cigarrillo es un comportamiento complejo que, junto con la intención de cambio, implican variables biopsicosociales y contextuales, que deben ser identificadas y consideradas en conjunto para hacer una mejor comprensión de lo que supone el cambio comportamental y poder establecer elementos efectivos de intervención, así como factores predictivos para el éxito de los procesos de cesación, tanto en población general como en grupos específicos (63,64). Los resultados complementan la información disponible sobre los factores vinculados al inicio y/o mantenimiento del consumo de tabaco, así como a la intención de cesación, favoreciendo la comprensión de la problemática de consumo y del cambio conductual requerido respecto de la cesación tabáquica en entornos universitarios.…”
Section: Conclusionesunclassified